2009
DOI: 10.1177/0734242x09355182
|View full text |Cite
|
Sign up to set email alerts
|

The pathway of in-situ ammonium removal from aerated municipal solid waste bioreactor: nitrification/denitrification or air stripping?

Abstract: In-situ ammonium removal from municipal solid waste (MSW) landfill is an attractive method due to its economic advantages. In this study, two simulated MSW bioreactors with different degrees of initial bio-stabilization were utilized to investigate the effects of intermittent aeration mode and the addition of activated sludge on the removal of ammonium. The results showed that up to 90% of ammonium could be removed and the amount of NO(x)-N produced was less than 1% of NH4 (+)-N removed in both reactors. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…-Several nitrogen transformation processes, such as nitrification, ammonia air stripping, favored under aerobic conditions (He and Shen, 2006;Hao et al, 2010). Hybrid -Combination of aerobic and anaerobic processes.…”
Section: Advantages Of Aerobic Bioreactor Landfillingmentioning
confidence: 99%
“…-Several nitrogen transformation processes, such as nitrification, ammonia air stripping, favored under aerobic conditions (He and Shen, 2006;Hao et al, 2010). Hybrid -Combination of aerobic and anaerobic processes.…”
Section: Advantages Of Aerobic Bioreactor Landfillingmentioning
confidence: 99%
“…Ammonia-nitrogen in a closed landfill is the key parameter that will affect the ability to release a landfill from regulatory oversight . Studies showed that in-situ aeration promoted a dramatic decrease in ammonia-nitrogen concentrations even under low biodegradable C/N conditions Hao et al, 2009). Heterogeneity of the waste environment does not always allow for uniform distribution of oxygen promoting the formation of anoxic and aerobic pockets.…”
Section: Aerobic Bioreactor Landfillmentioning
confidence: 99%
“…So far, investigations addressing the fate of nitrogen mainly focused on insitu aeration as a strategy to lower the concentration of NH 4 in landfill leachate, with numerous reports of significant NH 4 reduction in landfill leachate during and after in-situ aeration (e.g. Hao et al 2010;Hrad et al 2013;Prantl et al 2006;Ritzkowski et al 2006). The observed reduced nitrogen concentrations were explained by nitrification and denitrification processes within the waste body (Berge et al 2006;He et al 2006;Onay and Pohland 1998;Price et al 2003;Vigneron et al 2007).…”
Section: Introductionmentioning
confidence: 99%